NILAI MORAL DALAM NOVEL SURAT KECIL UNTUK TUHAN KARYA AGNES DAVONAR TINJAUAN PSIKOLOGI SASTRA - Yolanda Yolanda; Afif Rofii; Uli Wahyuni (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study was conducted with the aim of describing the moral values of human relationships with God from the aspects of praying, being grateful, and believing in God contained in the novel Surat Kecil untuk Tuhan by Agnes Davonar. This literary research was conducted in accordance with the scientific discipline that the researcher is studying in the field of Indonesian Language and Literature Education. To carry out this research, a descriptive research type with a qualitative approach was used. The type of qualitative descriptive research was used by the researcher as a method to describe the moral values of human relationships with God from the aspects of praying, being grateful, and believing in God which are depicted in the story of the novel Surat Kecil untuk Tuhan by Agnes Davonar. The data for this study were obtained by the researcher from quotations in the novel related to the aspects to be studied. From the results of this study, it can be concluded that in this novel, moral values of human relationships with God were found as many as 77 quotation data. The aspect of praying was found as many as 24 quotations, being grateful 27 quotations, and believing in God 26 quotations. This data can be explained that the three aspects of moral values are depicted in a balanced way in the story of this novel.